Electrochemical promoted CH bond chlorination of sulfoxonium ylides. (12th January 2023) - Zhang, Li-Ming; Fu, Zi-Hao; Yuan, Da-Fu; Guo, Ming-Zhong; Li, Ming; Wen, Li-Rong; Zhang, Lin-Bao
Graphical abstract: Abstract: The first electrochemical promoted CH bond chlorination of sulfoxonium ylides was accomplished using magnesium chloride as the chlorine source, as well as a supporting electrolyte. This method does not require transition metal catalysts, external oxidants, and electrolytes, providing a green and mild route for the functionalization of sulfoxonium ylides.